Efektivitas Video Edukasi Terhadap Pengetahuan dan Sikap Ibu Hamil Dalam Pencegahan Stunting di Puskesmas Sepaso - Anna Jalaili; Joko Sapto Pramono; Heni Suryani (Midwifery Care Journal, 2024)
Introduction : East Kutai district has a highest stunting incidence with 27.5%. Prevention for stunting beginning from early pregnancy to increase knowledge, attitudes and behavior of maternal because chronic energy deficiency during pregnancy can lead to stunting in children. Purpose of this study was to test the effectiveness of providing videos to pregnant women on knowledge and attitudes towards stunting prevention in Sepaso Health Center East Kalimantan in 2023thMethod : The study uses quasi-experimental design pretest-posttest design with control group. Population was pregnant women in Sepaso Health Center. Sampling technique was non-probabilistic sampling which counted 36 peoples.Results : The results of this study showed by bivariate analysis techniques using wilcoxon. In the experimental group with video, has Pvalue 0.000 (α) and in control group using leaflet, has Pvalue 0.001 (α)Conclusions : Mothers knowledge and attitudes regarding stunting have changed significantly after given health education with videos, so that its use can be further enhanced in health promotion